Analisis Cost-Minimization Terapi Dislipidemia: Perbandingan Obat Generik dan Bermerek di Fasilitas Kesehatan Tingkat Pertama - Vivi Olivia Sinapoy; Annissa Aprillia (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
Dyslipidemia is a major risk factor for cardiovascular disease and requires long-term therapy; therefore, cost efficiency is essential in primary health care facilities. This study aimed to analyze the cost comparison of dyslipidemia therapy using generic atorvastatin and branded atorvastatin (Lipitor) through a pharmacoeconomic approach employing cost-minimization analysis. The analysis was conducted from the primary health care perspective by considering direct medical costs, specifically the drug cost per patient. The study used secondary data based on national price estimates. The treatment regimen was atorvastatin 20 mg once daily. The results showed that generic atorvastatin had an estimated cost of approximately IDR 76,560 per month and IDR 931,480 per year, whereas Lipitor cost approximately IDR 780,720 per month and IDR 9,498,760 per year. The use of Lipitor required nearly ten times higher costs than the generic alternative, with a potential saving of about IDR 8.6 million per patient annually. In conclusion, generic atorvastatin is the most economically efficient therapeutic option without compromising clinical outcomes and supports policies promoting generic drug use to optimize health care financing.